2019
DOI: 10.1038/s41598-019-55588-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine model for assessing fetal and birth outcomes following transgestational maternal malaria infection

Abstract: Plasmodium falciparum infection during pregnancy is a major cause of severe maternal illness and neonatal mortality. Mouse models are important for the study of gestational malaria pathogenesis. When infected with Plasmodium chabaudi chabaudi AS in early gestation, several inbred mouse strains abort at midgestation. We report here that outbred Swiss Webster mice infected with P. chabaudi chabaudi AS in early gestation carry their pregnancies to term despite high parasite burden and malarial hemozoin accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
(140 reference statements)
2
4
0
Order By: Relevance
“…HO-1 has been shown to be elevated in plasma samples from infected pregnant women ( 59 ), and its mRNA expression was increased in the liver of pregnant BALB/c mice infected with P. berghei ANKA and conceptuses from C57BL/6 mice infected with P. chabaudi AS ( 60 , 61 ). Furthermore, a previous study found that conceptuses of Swiss mice infected with P. chabaudi AS displayed an increase in HO-1 mRNA that was correlated with hemozoin density in placental tissues, showing that higher tissue hemozoin levels are related to higher HO-1 expression ( 62 ), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…HO-1 has been shown to be elevated in plasma samples from infected pregnant women ( 59 ), and its mRNA expression was increased in the liver of pregnant BALB/c mice infected with P. berghei ANKA and conceptuses from C57BL/6 mice infected with P. chabaudi AS ( 60 , 61 ). Furthermore, a previous study found that conceptuses of Swiss mice infected with P. chabaudi AS displayed an increase in HO-1 mRNA that was correlated with hemozoin density in placental tissues, showing that higher tissue hemozoin levels are related to higher HO-1 expression ( 62 ), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…When the relationship between parasite burden and antioxidant gene transcript expression was considered, Cat and Hmox1 transcripts were positively correlated with placental parasitemia at sacrifice and Hmox1 shared this relationship with peripheral parasitemia AUC as well. These results are consistent with the observed strong association between Hmox1 expression and hemozoin deposition in the placentae of Pcc AS-infected Swiss Webster dams at midgestation [ 57 ]. Since E6.5 IP mice exhibited significant anemia and the greatest interval between infection and preterm delivery, infection initiated at this timepoint may present another opportunity to study the impact of Hmox1 regulation of heme in driving negative pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Although post-implantation Pcc infection in these models universally results in preterm labor, the results show that transcript abundance for certain genes in the placenta prior to labor differ based on the model. To our knowledge, these three models, combined with initiation of infection at E0.5 [21,22,25] are the first to provide the flexibility to probe the effect of malaria infection spanning the pre-implantation to the midgestation period in the mouse, without inducing maternal mortality. To varying extents, key features of human PM are recapitulated in these models, including severe maternal anemia, higher parasitemia in the placenta compared to the periphery, and preterm delivery [8,[20][21][22]24,25].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, these three models, combined with initiation of infection at E0.5 [21,22,25] are the first to provide the flexibility to probe the effect of malaria infection spanning the pre-implantation to the midgestation period in the mouse, without inducing maternal mortality. To varying extents, key features of human PM are recapitulated in these models, including severe maternal anemia, higher parasitemia in the placenta compared to the periphery, and preterm delivery [8,[20][21][22]24,25]. Indeed, in our 8.5 and 10.5 infection models, higher parasitemia in pregnant mice compared to non-pregnant controls corresponds with higher parasitemia in the placenta rather than the periphery, corroborating previous studies in both mice and humans demonstrating that pregnancy itself can increase susceptibility to malaria [4,27,28,41] and lead to parasite accumulation in the placenta [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation